Standards, Networks, and the Political Economy of International Lawmaking: A Response to Stavros Gadinis. (2015) - Stephan, Paul B.
Abstract : Three Pathways to Global Standards broadens our understanding of structures that undergird international cooperation. Stavros Gadinis argues that different kinds of lawmaking networks propagate differently. Private networks depend on market success, in the sense that the demand for their products rests on competition in the private sector. Regulators succeed when they cooperate with true peers. States use power to work their will. I have some second-order criticisms of the article, offered in the spirit of respectful engagement with good scholarship. These reservations, however, do not detract from a view that Gadinis has identified significant issues in international relations and has proposed useful theses about them as well as good strategies for their validation.